2017
DOI: 10.3233/cbm-170188
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Long non-coding RNA HULC promotes bladder cancer cells proliferation but inhibits apoptosis via regulation of ZIC2 and PI3K/AKT signaling pathway

Abstract: LncRNA HULC promoted bladder cancer cells proliferation and inhibited apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…As indicated by a number of studies, lncRNA HULC is highly upregulated in liver cancer [44], functions as an oncogene in epithelial ovarian carcinoma [45], promotes proliferation and inhibits apoptosis in bladder cancer [46], and attenuates the chemosensitivity of hepatocellular carcinoma cells [47]. In the current study, a marked downregulation was observed in HULC expression in MDA-MB-231 cells after CCT137690 treatment.…”
Section: Discussionsupporting
confidence: 60%
“…As indicated by a number of studies, lncRNA HULC is highly upregulated in liver cancer [44], functions as an oncogene in epithelial ovarian carcinoma [45], promotes proliferation and inhibits apoptosis in bladder cancer [46], and attenuates the chemosensitivity of hepatocellular carcinoma cells [47]. In the current study, a marked downregulation was observed in HULC expression in MDA-MB-231 cells after CCT137690 treatment.…”
Section: Discussionsupporting
confidence: 60%
“…And the overall genetic alterations of PIK3CA (24%) are described in BLCA (Table 1). It is further shown that PPARγ, Sema4D, CCDC34, miR-29c, -143, -145 and -294, as well as LncRNA ATB, LINC00641, HULC, DUXAP10 and UCA1 regulate proliferation, migration, or invasion of BLCA cells via PI3K/AKT pathway [275][276][277][278][279][280][281][282][283][284][285]. Even though there is a significant unmet need for new therapies, however, at present only a small amount of clinical trials of BKM120 and GSK2636771 try to find out what PI3K inhibitor's prospects bring to the BLCA patients (Table 2).…”
Section: Dysregulation Of the Pi3k/akt Pathway In The Genitourinary Smentioning
confidence: 95%
“…As an oncogene, HULC has also been proved to play a critical role in regulating tumor metastasis in colorectal cancer, 15 hepatocellular carcinoma, 16 and bladder cancer. 17 Wang et al revealed that the expression of HULC was upregulated in cervical cancer, and associated with overall survival, 11 indicating that HULC may serve as a predictive biomarker for the prognosis of cervical cancer. In the present study, our data also demonstrated that HULC had high expression in cervical cancer cells, which is consistent with the findings showing HULC upregulation in cervical cancer tissues.…”
Section: Discussionmentioning
confidence: 99%